1981
DOI: 10.1080/03014468100005231
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal comparison of aerobic power in active and inactive boys aged 7·0 to 17·0 years

Abstract: Height and maximal aerobic power (VO2 max) were analysed longitudinally in 14 active and 11 inactive boys from the Saskatchewan Longitudinal Growth Study. VO2 max values were obtained from a treadmill run repeated each year. The Preece-Baines Model I was fitted to height and VO2 max values over the duration of the study. No significant differences were found for height attained between the two groups. VO2 max comparisons revealed no significant differences before the take-off point for the adolescent growth sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
5
8

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 10 publications
2
55
5
8
Order By: Relevance
“…Nevertheless, it is reasonable to suggest that the age range of the players who participated in our study (13.0 -16.1 years) can be considered very "sensitive" to VO 2 max improvements. In fact, the largest increases, even in untrained individuals, generally occur between the ages of 13-to 14 and 14-to 15-years old [40], reaching an average increase of 38% as measured in approximately 80 male adolescents of the same age range [41]. This data accounts for the significant alterations found in our sample.…”
Section: Discussionsupporting
confidence: 72%
“…Nevertheless, it is reasonable to suggest that the age range of the players who participated in our study (13.0 -16.1 years) can be considered very "sensitive" to VO 2 max improvements. In fact, the largest increases, even in untrained individuals, generally occur between the ages of 13-to 14 and 14-to 15-years old [40], reaching an average increase of 38% as measured in approximately 80 male adolescents of the same age range [41]. This data accounts for the significant alterations found in our sample.…”
Section: Discussionsupporting
confidence: 72%
“…Some of these studies (Bar-Or and Zwiren 1973;Schmuecker and Hollmann 1973;Kobayashi et al 1978;Yoshida et al 1980;Mirwald et al 1981) did not reveal any traininginduced improvement before the onset of puberty, although others (Brown et al 1972;Weber et al 1976;Lussier and Buskirk 1977;Vaccaro and Clarke 1978;Gerhardus 1980;Petratis et al 1983;Rotstein et al 1986;Mahon and Vaccaro 1994) revealed absolutely the opposite. Similarly, Ekblom (1969), Eriksson (1972), Massicotte and MacNab (1974), Kobayashi et al (1978), Mirwald et al (1981) and Mahon and Vaccaro (1989) observed a positive effect of training during pu-great increase in V _ O 2max observed during pubertal growth, which follows the stage of peak height velocity (Kobayashi et al 1978;Kemper and Verschuur 1981;Mirwald et al 1981;Krahenbuhl et al 1985;Paterson et al 1986), which is complicated by the deviation between the subjects' chronological and biological age. If groups of the same biological maturation are not compared it is not easy to isolate the training effect from the differentiation caused by growth, especially during the stage of peak growth velocity.…”
Section: Introductionmentioning
confidence: 91%
“…Segundo Mirwald et al (41) e Marques et al (40) , os valores médios, nas provas de resistência aeróbica avaliadas indirectamente aumentam com a idade.…”
Section: Resistência Aeróbicaunclassified
“…Com o aparecimento da puberdade, os rapazes mostram um aumento da potência aeróbica que está claramente relacionado com o pico de velocidade da altura (41) . Borms (13) confirma este aspecto ao referir que nos rapazes atletas, após os 12 anos de idade, há um aumento na sensibilidade ao treino do sistema cárdio-circulatório, decorrendo daqui um aumento da capacidade aeróbica.…”
Section: Resistência Aeróbicaunclassified